2015
DOI: 10.1371/journal.pone.0128682
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Changes in Resting-State EEG as Potential Biomarker for Amyotrophic Lateral Sclerosis

Abstract: BackgroundAmyotrophic Lateral Sclerosis (ALS) is heterogeneous and overlaps with frontotemporal dementia. Spectral EEG can predict damage in structural and functional networks in frontotemporal dementia but has never been applied to ALS.Methods18 incident ALS patients with normal cognition and 17 age matched controls underwent 128 channel EEG and neuropsychology assessment. The EEG data was analyzed using FieldTrip software in MATLAB to calculate simple connectivity measures and scalp network measures. sLORETA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 20 publications
6
52
0
Order By: Relevance
“…This is in contrast with the study by Iyer and colleagues14, who used a set of connectivity metrics in combination with network analysis. In contrast to their work, we used different methods of functional connectivity (PLI) and network reconstruction (MST), as well as a conservative statistical approach.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This is in contrast with the study by Iyer and colleagues14, who used a set of connectivity metrics in combination with network analysis. In contrast to their work, we used different methods of functional connectivity (PLI) and network reconstruction (MST), as well as a conservative statistical approach.…”
Section: Discussionmentioning
confidence: 77%
“…Other resting-state fMRI studies111213 have reported alterations in specific resting-state networks. Recently, Iyer and colleagues14 have investigated the use of resting-state electroencephalographic (EEG) as a potential biomarker for ALS, suggesting that a pathologic disruption of the network can be observed in early stages of the disease. However, it still remains relevant to address methodological issues that may affect both connectivity estimation and network reconstruction15.…”
mentioning
confidence: 99%
“…Characteristic patterned changes of cortical function in ALS signify widespread disease-associated network disruption, pointing to extensive dysfunction of both motor and cognitive networks. Clinical and neuroimaging evidence confirms extensive involvement of motor (Douaud et al, 2011;Nasseroleslami et al, 2019;Proudfoot, van Ede, et al, 2018) and cognitive (Iyer et al, 2015;McMackin, Dukic, et al, 2019) pathways and networks. (Hardiman, Van Den Berg, & Kiernan, 2011).…”
mentioning
confidence: 72%
“…Previous EEG studies have shown altered patterns, such as increased frontal-to-parietal connectivity in ALS (Blain-Moraes, Mashour, Lee, Huggins, & Lee, 2013;Iyer et al, 2015;Nasseroleslami et al, 2019). To date, however, there have been limited attempts to localise abnormal EEG patterns to specific brain regions.…”
mentioning
confidence: 99%
“…Dysphagia has also been reported in humans following the administration of either benzodiazepines 38– 40 or alcohol 41 . Administration of benzodiazepines reduces voluntary saccadic eye movement function 42 and increases EEG beta-wave activity 42 , clinical manifestations that also occur in neuromuscular and neurological diseases 18, 43, 44 . Increased GABAergic inhibitory activity can also cause bladder 45, 46 and gastrointestinal dysfunction 47, 48 , both of which can manifest in neuromuscular and neurological diseases 1921 .…”
Section: The Clinical Features Of Neuromuscular and Neurological Disementioning
confidence: 99%